PARTICIPATIVE MAINTENANCE OF UPSTREAM PUSUR SUB WATERSHED AREA THROUGH CONSERVATION FIELD SCHOOL IN MRIYAN VILLAGE MUSUK SUB DISTRICT BOYOLALI REGENCY - Muslim Afandi (Islamic Studies Journal for Social Transformation, 2017)
This research is done to describe the process of participative maintenance by ‘sekolah lapang konservasi’ in the upstream area of Sub Watershed Pusur, so we can understand the condition of Farmers in the Mriyan village, and to understand the impact of the participative maintenance of Sub watershed Pusur in the Mriyan village that will be observed from the actualization of farmer participation in Mriyan Village. This research used qualitative approach with descriptive strategy in Mriyan Villages Sub District Musuk District Boyolali. The location is choosen because of the topography of the area as a water absorption area and water catchment area along the Sub Watershed Pusur. The data collection technique uses in depth interview method, focus group discussion, and participative observation. After all the data is collected, then data will be analyzed to form a finding that Skolah Lapang Konservasi is a kind of community participation in Mriyan village in maintaining Sub watershed Pusur conservatively. The people of Mriyan’s support is actualized in the form of konservasi field school, the effort and the decision making, that are actively in charge in social learning, net working, and maintaining the resource of thee people. From this thing, the maintenance will impact various aspect, such as: the sustainability of Sub Watershed Pusur, the emergence of collective institutional of the people who care about Sub watershed Pusur, and pushing the stakeholders in caring for Sub Watershed Pusur with the principality of conservation.